Formas de violência contra mulheres lésbicas: um estudo sobre percepções, discursos e práticas - Melo, Mariana Soares Pires (2016)
The present dissertation seeks to reflect about the various forms of violence practiced against lesbian women, analyzing these processes in their perceptions and how they influence the construction of their discourses and practices. Therefore, in-depth interviews were conducted with ten women who identified themselves as lesbians in order to observe violent processes in their narratives, as well as the ways in which they perceive and deal with them, recognizing that such processes act directly in their constructions as subjects or "non-subjects", on their relationships with other individuals and social institutions. We reflect on the category of violence directly connected with issues of gender and sexuality, especially dialoguing with Michel Foucault, Judith Butler and the sociology of deviance.